Post-accidental structural reliability of double-hull oil tanker with near realistic collision damage shapes. (30th December 2020) - Parunov, Joško; Prebeg, Pero; Rudan, Smiljko
ABSTRACT: The consequence of the near realistic modelling of collision damage shape on the post-accidental ultimate hull girder strength of double-hull oil tanker is investigated. For known striking ship's geometry of the bulbous bow, damaged elements are removed from the finite element model of the midship section of the struck ship. Progressive finite element collapse analysis is then performed to determine residual strength index (RSI) of damaged ship. The analysis is performed for set of 50 collision scenarios, obtained from the historical ship collision database. In addition, probabilistic analysis of RSI is performed by approximating damage shape as 'rectangular box', based on IMO and GOLADS project. Structural reliability analysis is then employed to assess the consequences of various modelling assumptions used in RSI computations. Results of the analysis show that near realistic modelling of damage shape results in much lower failure probability of damaged ship compared to the 'rectangular box' models.